2015
DOI: 10.24059/olj.v19i5.694
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of an Online Tutoring Program’s Impact on Low-Achieving Middle School Students’ Mathematics Achievement

Abstract: The purpose of this mixed methods study was to determine the impact of synchronous online tutoring services on struggling middle school students' mathematics achievement. The online tutoring was provided as a response to intervention (RTI) Tier 3 support (intensive, individualized intervention) in schools implementing a school-wide mathematics program that addresses Tier 1 (high-quality classroom instruction) and Tier 2 (small group interventions). We employed quasi-experimental, within-and between-group desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
44

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 24 publications
(33 reference statements)
2
25
1
44
Order By: Relevance
“…The findings from this study aligned with previous studies that demonstrated positive effects associated with the use of supplemental digital resources and students' mathematics performance among students at the elementary, intermediate, and junior high levels (e.g., Chappell, Arnold, Nunnery, & Grant, 2015;Clark & Whetstone, 2014;Kiriakidis & Geer, 2014;Martindale et al, 2005;Nunnery & Ross, 2007;Ysseldyke & Bolt, 2007). Among each campus level, Think Through Math © usage accounted for more than half of the variance in students' STAAR mathematics assessment scores than would be explained by chance.…”
Section: Discussionsupporting
confidence: 88%
“…The findings from this study aligned with previous studies that demonstrated positive effects associated with the use of supplemental digital resources and students' mathematics performance among students at the elementary, intermediate, and junior high levels (e.g., Chappell, Arnold, Nunnery, & Grant, 2015;Clark & Whetstone, 2014;Kiriakidis & Geer, 2014;Martindale et al, 2005;Nunnery & Ross, 2007;Ysseldyke & Bolt, 2007). Among each campus level, Think Through Math © usage accounted for more than half of the variance in students' STAAR mathematics assessment scores than would be explained by chance.…”
Section: Discussionsupporting
confidence: 88%
“…The tutees were generally positive about their experiences, particularly with respect to their learning improvement and social interactions with tutors. The tutees also offered a few negative comments about the slow pace of the instruction and the need for clearer explanations (Chappell et al, 2015). These findings are consistent with those of similar studies and confirm that struggling students benefit from individualized and focused tutoring (Burch et al, 2016).…”
Section: Effectiveness Of Digital Tutoringsupporting
confidence: 83%
“…Most of the previous literature discussing digital tutoring emphasized tutor training and relationship building (Chappell et al, 2015). This research contributes to the understanding of digital tutoring and social capital by highlighting strategies for developing social capital in after-school digital tutoring programs.…”
Section: Implications and Conclusionmentioning
confidence: 89%
See 2 more Smart Citations